THE ALIGNMENT OF GRADUATE PROFILES OF THE BUILDING ENGINEERING EDUCATION PROGRAM WITH WORKFORCE REQUIREMENTS BASED ON ALUMNI AND EMPLOYER PERCEPTIONS - Gde Agus Yudha Prawira Adistana; Wahyu Dwi Mulyono; Agus Wiyono; Mochammad Rafli Aziz (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
In the context of performance evaluation to enhance competitiveness and the quality of higher education institutions, it is necessary to identify performance indicators, one of which is the quantity, quality, and relevance of graduates. This study aims to optimize tracer studies as an effort to improve the quality of education in the Bachelor of Building Engineering Education Program, Faculty of Engineering, Unesa. A tracer study is research on the situation of alumni, particularly regarding job searches, work situations, and the utilization of competencies acquired during their studies in the Bachelor of Building Engineering Education Program, Faculty of Engineering, Unesa. This research is planned for the year 2024, targeting alumni who graduated in 2022. The method used in this research is descriptive with a quantitative approach. The tracking is conducted by involving surveyors to encourage alumni to fill out questionnaires on the tracer study platform directly provided by the university. The results of this tracer study are then analyzed across several components to provide input for the study program to improve its future performance. The findings of this study are as follows: (1) most graduates of the Bachelor of Building Engineering Education Program are employed in private companies. The alignment between the graduates' jobs and the graduate profile of the Bachelor of Building Engineering Education Program shows a 60% match, (2) the work skills possessed and required by graduates of the Bachelor of Building Engineering Education Program show similar results, but work skills applied in the workplace show higher scores, (3) employer assessments regarding performance fall into the good category, and work skills are also categorized as good.